International taxation & domestic taxation: determining 'source' within and out of an e-commerce environment - Bardopoulos, Anne (Centre for Law and Society, 2026)
This paper deals with the relationship between domestic tax laws and double tax treaties with respect to transactions occurring in an E-commerce environment. In order to understand the taxing consequences arising from an E-commerce transaction, the taxing consequences of international transactions outside of an E-commerce environment must also be examined and explored. Furthermore, this paper is primarily concerned with determining the "source" of income arising from international transactions and, more specifically, E-commerce transactions. As such, both domestic legislation and case will be examined in conjunction with double tax treaties and Commentary published by the Organisation for Economic Co-operation and Development. The international community's position on the matter will examined in conjunction with a brief overview of suggested solutions and problems arising and facing the international community in relation to the phenomenon that is the Internet.